INTERNATIONAL LEGAL PERSPECTIVES ON CIVIL LIABILITY FOR NUCLEAR DAMAGE (International Journal of Food and Nutritional Sciences, 2022)
In 1986 a nuclear accident occurred at the Chernobyl Nuclear Power Plant in Ukraine that would have a profound impact on the evolution of international nuclear liability law. The accident had a serious detrimental effect on human health, property and the natural environment and damage was suffered not only in Ukraine itself but in several neighboring countries and some cases far beyond. Nuclear-related activities create risks for a specific character. The 1986 Chornobyl accident confirmed prior theoretical assessments that a nuclear accident might cause damage of an extreme magnitude. The detrimental effects of such an accident do not stop at state borders; they may extend into regions far beyond the territory of the accident state. There may be damage to an individual's property and the environment in several States. The damage caused by ionizing radiation to living cells, especially humans, may not be immediately recognizable; it may be latent for a long time. Since the radiation doses received by living cells have cumulative effects, there may be damage caused by different sources of radiation. In many cases, there is no typical radiation injury. Moreover, cancer may result from a radiological accident or from, for example, smoking .